Fiqh Muamalah Analysis of Paylater Systems: Behavioral Control, Impulse Buying, and Sharia Compliance - Najma Taralia Farah; Afdawaiza Afdawaiza; Ahmad Sarjon Razik; Abdullah Ali Al Makky; Dind Ibra Benign Sajid (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2026)
The rise of paylater as a dominant payment feature in Indonesian e-commerce and e-wallet platforms has triggered notable shifts in how consumers make purchase decisions. This study explores, through a qualitative literature approach, how paylater weakens behavioral control particularly perceived behavioral control within the Theory of Planned Behavior and accelerates impulse buying tendencies. When payment friction is reduced to a single tap, the psychological cost of spending diminishes, making unplanned purchases feel deceptively rational. Findings further indicate that impulse buying, when paired with satisfying post-purchase experiences, mediates repurchase intention. However, this cycle is fragile post-purchase regret can just as easily sever platform loyalty. From an Islamic economic lens, paylater raises unresolved concerns regarding transparency, interest-like penalties, and the promotion of israf. The study concludes that the behavioral consequences of financial technology design deserve more critical attention.